Pemikiran Syekh Hasyim Asy'ari tentang Penguatan Pendidikan Karakter Islami di Sekolah Dasar: Systematic Literature Review - Abdul Aziz Binsa; Mohamad Salik (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examines the relevance of KH. Hasyim Asy'ari's thinking on character education for the context of Elementary Schools/Islamic Elementary Schools (SD/MI) through a Systematic Literature Review (SLR). Analysis of a number of literatures found that Asy'ari's concept of character, which is based on the book "Adab al-‘Ālim wa al-Muta‘allim," is holistic and built on three main pillars. First, a philosophical foundation that views character education as tazkiyatun nafs (purification of the soul) with an emphasis on developing inner motivations such as sincerity and humility. Second, a relational model that places the relationship between teacher (murabbi) and student based on example and respect as the central mechanism for instilling values. Third, an operational framework that implements abstract values ​​through micro-habits (ta'dīb) in school routines and thematic integration into the national curriculum. This synthesis produces a conceptual framework that shows that Asy'ari's thoughts can function as a value amplifier that enriches and deepens the practice of character education in elementary schools/Islamic elementary schools, bridging the values ​​of Islamic boarding schools with the demands of modern education to form a generation that is intelligent and has noble morals.